Transcranial magnetic stimulation therapy for central post-stroke pain: systematic review and meta-analysis - Gurdiel-Álvarez, Francisco; Navarro-López, Víctor; Varela-Rodríguez, Sergio; Juárez-Vela, Raúl; Cobos-Rincón, Ana; Sánchez-González, Juan Luis (Frontiers in Neuroscience, 2024)
Introduction Although rare, central post-stroke pain remains one of the most refractory forms of neuropathic pain. It has been reported that repetitive transcranial magnetic stimulation (rTMS) may be effective in these cases of pain. Aim The aim of this study was to investigate the efficacy of rTMS in patients with central post-stroke pain (CPSP). Methods We included randomized controlled trials or Controlled Trials published until October 3rd, 2022, which studied the effect of rTMS compared to placebo in CPSP. We included studies of adult patients (>18 years) with a clinical diagnosis of stroke, in which the intervention consisted of the application of rTMS to treat CSP. Results Nine studies were included in the qualitative analysis; 6 studies (4 RCT and 2 non-RCT), with 180 participants, were included in the quantitative analysis. A significant reduction in CPSP was found in favor of rTMS compared with sham, with a large effect size (SMD: −1.45; 95% CI: −1.87; −1.03; p < 0.001; I2: 58%). Conclusion The findings of the present systematic review with meta-analysis suggest that there is low quality evidence for the effectiveness of rTMS in reducing CPSP. Systematic review registration Identifier (CRD42022365655).